Influence of the Xanthine Derivate HWA 138 on Endotoxin-Related Coagulation Disturbances: Effects in Non-Sensitized vs D-Galactosamine Sensitized Rats - Bahrami, Soheyl; Redl, H; Buurman, W A; Schlag, G (Thrombosis and Haemostasis, 1992)
We have evaluated the effects of the xanthine derivate HWA 138 in rat endotoxemia in order to 1) prevent coagulation disturbances and other endotoxin-induced physiological abnormalities and 2) to reduce mortality. We performed two studies using two different models (sensitized vs non-sensitized rats) with a similar mortality but different severity of coagulation disturbances: a) LPS (15 mg/kg) alone or with HWA 138 (80 mg/kg) as a treatment modality 30 min pre LPS, b) galactosamine (500 mg/ kg) simultaneously with LPS (100 µg/kg) with or without HWA 138 (80 mg/kg) pretreatment. Experiments c) and d) employed D-galactosamine and/or LPS similar to experiments a) and b), while HWA 138 was applied simultaneously. We found significant 1) amelioration of life-threatening coagulation disturbances in non-sensitized rats, 2) prevention of liver dysfunction in sensitized rats, 3) reduction of TNF formation in both models, and 4) improvement of survival in all groups receiving HWA 138. Our data indicate protective effects of HWA 138 against clotting disturbances either directly via reduced LPS-induced formation of procoagulant activity or indirectly via reduced TNF formation.